Analysis of the Development of China’s Long-term Care System - Chen, Mengxuan (Glasnik Advokatske komore Vojvodine, 2024)
China is entering a stage of rapid ageing development. Due to its large population base and the implementation of the one-child policy for more than 30 years, China is ageing faster than other countries, with a larger number of elderly people and facing more urgent problems of elderly care and traditional home care is no longer sustainable which increasing the need for long-term care. China began exploring long-term care with the "Long-Term Medical Care Insurance System" in Qingdao in 2012. In 2016, pilot cities were initiated in 15 regions, expanding to 49 cities in September 2020 with the issuance of a directive for expansion. However, to date, there is no unified long-term care system at the national level and no long-term care law has been established as a legal safeguard. Even though everyone may need long-term care, based on the current coverage of the Chinese long-term care system, this paper will focus on elderly people. The purpose of this paper is to sort out the development status and problems of China’s long-term care system in the past ten years. The following two questions will be answered: 1. What is the current status of Chinese Long-term care? and 2. What are the concerns of the Chinese Long-term care system?